AD, Volume 20, n° 2, 1995 - Full Issue - Journal System (Africa Development, 1995)
Contents Parallel Trade and Powerless Places: Research Traditions and Local Realities in Rural Northern Nigeria Kate Meagher ............................ 5 Technology Development and Dissemination in Agriculture: A Critique of the Dominant Model Erasmus D. Monu .......................... 21 Le capital de confiance initial des régimes militaires africains Niandou Souley Abdoulaye ............................. 41 Militaires et militarisme en Afrique: cas du Burkina Faso Basile Laetare Guissou ............................... 55 Towards an Analysis of IMF Structural Adjustment Programmes in Sub-Saharan Africa (SSA): The Case of Zimbabwe 1990-1994 A. S. Mlambo .................................... 77 Scientific Ethos, Authoritarian Regimes and Social Change in Sub-Saharan Africa Adebayo Ninalowo ................................ 99 Book Review Cultural Nationalism and Western Hegemony: A Review Essay on Appiah's Universalism Kolawole Aderemi Owolabi ........................ 113 Publications Received and Acquired ........................... 125